1998
DOI: 10.1177/107424849800300107
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Reactive Oxygen Species in Various Vascular Cells During Glyceryltrinitrate Metabolism

Abstract: BACKGROUND: Anti-ischemic therapy with organic nitrates as nitric oxide (NO) donors is complicated by the induction of tolerance. When nitrates are metabolized to release NO, there is a considerable coproduction of reactive oxygen species (superoxide radical and peroxynitrite) in vessels leading to inactivation of NO, to diminished cyclic quanosine monophosphate production in smooth muscle cells (SMC), to impaired vasomotor responses to the endothelium-derived relaxation factor (EDRF), and to formation of nitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 58 publications
2
22
0
Order By: Relevance
“…Local redox poise might be another factor. Tissue antioxidant content has been shown to influence constitutive nitroso͞nitrosyl levels (15), and GTN biotransformation can stimulate the production of superoxide anions, whose avid reactivity with NO is believed to contribute to nitrovasodilator tolerance and pathological NO insufficiency (39). Evaluation of the extent to which these and other factors govern the tissue-specific dynamics of the GTN NObonome awaits further study.…”
Section: Discussionmentioning
confidence: 99%
“…Local redox poise might be another factor. Tissue antioxidant content has been shown to influence constitutive nitroso͞nitrosyl levels (15), and GTN biotransformation can stimulate the production of superoxide anions, whose avid reactivity with NO is believed to contribute to nitrovasodilator tolerance and pathological NO insufficiency (39). Evaluation of the extent to which these and other factors govern the tissue-specific dynamics of the GTN NObonome awaits further study.…”
Section: Discussionmentioning
confidence: 99%
“…An unavoidable superoxide source may be GTN itself, which was shown to trigger superoxide formation in blood vessels, thereby limiting vascular NO bioavailability (33)(34)(35). In addition, we found that DTT, which was present to minimize mechanism-based oxidative ALDH inactivation, caused rapid consumption of authentic (DEA/NO-derived) NO that was prevented by superoxide dismutase.…”
Section: Discussionmentioning
confidence: 99%
“…While the means by which ascorbate prevents tolerance remain to be determined, others have suggested that Vit-C could ( a ) directly affect superoxide production by the NADPH oxidoreductase; ( b ) scavenge superoxide directly, and thereby decrease nitric oxide inactivation; ( c ) increase ni- trosothiol formation by protecting plasma thiols from oxidation; and ( d ) suppress peroxynitrite-mediated inactivation of target enzymes (4,7,(13)(14)(15)(16)(17)(27)(28)(29). Other factors, including possible effects on GTN biotransformation, the neurohumoral axis, prostacyclin generation, leukocyte aggregation, oxidized LDL generation, or platelet-activating factor mimetics, cannot be ruled out (30)(31)(32)(33)(34)(35)(36).…”
Section: Discussionmentioning
confidence: 99%